Insights into future therapeutics for atopic dermatitis. (11th February 2018) - Edwards, Taylor; Patel, Nupur U.; Blake, Amy; Prabakaran, Samantha; Reimer, Danielle; Feldman, Steven R.; Strowd, Lindsay C.
ABSTRACT: Introduction : Atopic Dermatitis (AD) is a common chronic inflammatory skin disorder with a constellation of symptoms. Currently, there are numerous therapies in various phases of drug development that target the pathogenesis of AD. Areas covered : Our paper aims to examine small molecule therapies and other novel agents registered for clinical trial in the phase II and mainly phase III stages of development. A literature search using PubMed as well as Clinicaltrials.gov was conducted. Clinical trial evidence of these novel agents was compiled and assessed. Both topical and oral novel therapies with diverse range of mechanistic action are currently being studied, with varying success. These include phosphodiesterase-4 inhibitors, boron molecules, Janus kinase inhibitors, cannabinoid receptors agonists, kappa-opioid receptor agonists. A variety of compounds with yet undisclosed or unknown mechanisms of action are also being studied. Expert opinion : Further research through extensive clinical trials will allow for more information about these targeted therapies and their potential place in the treatment algorithm of AD. Due to the success of such therapies in treating a spectrum of chronic inflammatory diseases, we remain hopeful that the successful development of targeted therapy for AD lies ahead.